Irrigation frequency and vermiculite proportion in substrate for Eucalyptus grandis seedling - Cruz, Gustavo Henrique Miguel da; Cunha, Fernando França da; Souza, Epitácio José de; Silva, Andrisley Joaquim da; Filgueiras, Roberto; Silva, Francisco Charles dos Santos (Semina: Ciências Agrárias, 2020)
This study aimed to determine the best irrigation frequency and vermiculite proportion in substrate for Eucalyptus grandis seedling production in poorly technified nurseries. The experiment was carried out in Chapadão do Sul - MS (Brazil) from April 8 to July 23, 2013 (106 days). The experimental design was in randomized blocks arranged in a split-plots, with four irrigation frequencies (plots) and five vermiculite proportions (subplots) and six replications. Irrigation depth was estimated by the reference evapotranspiration (Penman-Monteith) multiplied by a crop coefficient (Kc) of 2. Average daily irrigation depth was 5.5 mm during the experimental period. The results showed that two daily irrigations (at 11:00 a.m. and 7:00 p.m.) and filling tubes with 80% vermiculite and 20% soil were most suitable for eucalyptus seedling production under these experimental conditions.